The Instrumentalization of Public Action in Higher Education in Argentina. Policies Around Academic Work and Collective Bargaining - Pérez, Pedro Enrique; Solanas, Facundo (Íconos, 2015)
From the different changes that have occurred since the 1990s, at the international as well as the national levels, this article attempts to first and foremost analyze the measures introduced in relation to higher education in the case of Argentina. Secondly, with the crisis of the neoliberal paradigm there has been re-composition and wage equalization, accompanied by development measures and strengthening of the academic profession. These changes need to be understood within the context of the agenda of joint-regulation of academic labor relations. Drawing upon the analytical tools in public policy analysis, this study analyzes primary documents in order to establish the continuities and changes in the measures that have been implemented in Argentina. To this end, we analyze the national joint negotiations in general and the specific case of the joint negotiations in the National University of Mar del Plata.